1998
DOI: 10.1021/la9707639
|View full text |Cite
|
Sign up to set email alerts
|

Desorption of 4-Aminobenzenethiol Bound to a Gold Surface

Abstract: Desorption of 4-aminobenzenethiol (ABT) bound to a gold surface in bulk ethanol solution was studied by the measurement of the UV-absorption of the solution, from the points of both thermodynamics and kinetics. By eliminating the kinetic effects, we evaluated the equilibrium ratio of the adsorbed species with respect to the initial concentration of ABT in the solution. We found that the gold surface is fully covered by ABT above the bulk concentration of 0.5 mmol/dm3. By analyzing the kinetics of the surface r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 35 publications
1
47
0
Order By: Relevance
“…In this method, the behaviour of thiol molecules on gold is studied during the desorption process [50]. Existence of dimer molecules on the surface has been reported by Mohri et al [51] which is in agreement with the SPR studies of Kajikawa et al [30]. Using a comprehensive TDS study, Noh et al [52] explained the existence of different adsorption sites and showed that dimerization plays a major role in SAM formation and desorption.…”
Section: Thermal Desorption Spectroscopy (Tds)supporting
confidence: 58%
“…In this method, the behaviour of thiol molecules on gold is studied during the desorption process [50]. Existence of dimer molecules on the surface has been reported by Mohri et al [51] which is in agreement with the SPR studies of Kajikawa et al [30]. Using a comprehensive TDS study, Noh et al [52] explained the existence of different adsorption sites and showed that dimerization plays a major role in SAM formation and desorption.…”
Section: Thermal Desorption Spectroscopy (Tds)supporting
confidence: 58%
“…[reference] are the estimated number of molecules in the enhanced and reference samples, respectively. The number of molecules in the sample was estimated by using the average number of nanoshells per spot, the surface area of the nanoshell, and the packing density of pMA on the nanoshell surface (35). This analysis assumes that the entire nanoshell surface area contributes to the Raman response and is a conservative estimate, essentially a lower bound, of the Raman enhancement.…”
Section: Figmentioning
confidence: 99%
“…Therefore, the measured Raman response should be proportional to ͉E shell ( o )͉ 2 ͉E Raman ( s )͉ 2 . This SERS optimization factor, ͉E shell ( o )͉ 2 ͉E Raman ( s )͉ 2 , is then calculated at each point on the nanoshell surface, assuming a monolayer of a molecule covering the surface of the nanoshell, and allowing for a coverage of 0.3 nm 2 per molecule (35).…”
Section: Figmentioning
confidence: 99%
“…9 The adsorption of the tetrathiol resorcinarenes to the nanoparticles was expected to be robust, given the multivalent nature of the surfactants 10 and the very low rates of desorption of aryl monothiols from gold surfaces. 11 Aqueous solutions of citrate-stabilized 20-nm gold nanoparticles were treated with millimolar solutions of 1 in THF and extracted several times against toluene. Evaporation of the solvent resulted in a blue film at the solvent interface, which was directly transferred by horizontal (Langmuir-Schaefer) deposition onto a carbon-coated copper grid.…”
Section: Resultsmentioning
confidence: 99%